Petrografia e geoquímica do Complexo Uraricoera, embasamento da porção central do Escudo das Guianas, noroeste do Estado de Roraima - Macêdo, Bruna Yumi Iimori (Brasil, 2023)
The objective of this project was the petrographic and geochemical characterization of the rocks of the Uraricoera Complex, an orthoderived basement of the northwest portion of the state of Roraima, leading to its subdivision into 5 main lithofacies: (1) biotite-hornblende metagranites and gneisses; (2) biotite metagranites and gneisses; (3) biotite meta quartz syenites; (4) granulites; and (5) metadiorites and amphibolites. In general terms, these rocks have chemistry similar to type-I granitic associations, subalkaline, metaluminous to weakly peraluminous, with calcium-alkaline affinity, probably related to a volcanic arc environment. From the existing microstructures, it was possible to infer a high-grade metamorphism with a peak in granulite facies, in addition to two retrometamorphisms, one in amphibolite to greenschist facies, and another in greenschist to prehnite-pumpellyite facies.